2007
DOI: 10.1007/s11666-007-9072-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Protection Properties by Using Nanostructured Ceramic Powders for HVOF Coatings

Abstract: The potential of the high-velocity oxy-fuel (HVOF) thermal spray process for reduced porosity in coatings compared to those produced by other ambient thermal spray processes is well known. The ability to produce high-density ceramic coatings offers potential in high-performance applications in the field of wear, corrosion resistance, and dielectric coatings. However, due to operational limit of the HVOF process to effectively melt the ceramic particles, the process-structure relationship must be well optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In a recent work Bakan et al 9 demonstrated that YbDS coatings with porosities below 10% and relatively high crystallinity of more than 30% could be produced by high velocity oxygen fuel spraying (HVOF). This is in accordance to prior works where coatings from ceramic materials such as alumina, chromia, titania, or even hydroxyapatite with high degrees of crystallinity and high phase purity could be achieved by HVOF deposition starting from small-sized or nano-agglomerated feedstocks [10][11][12][13] . All studies concluded that dense ceramic coatings can be obtained with sufficient deposition efficiency only if particles are melted sufficiently so that good adhesion between the deposited splats is achieved, while crystallinity in the coating depends mainly on the amount of partially unmelted powder particles.…”
Section: Accepted Articlesupporting
confidence: 90%
“…In a recent work Bakan et al 9 demonstrated that YbDS coatings with porosities below 10% and relatively high crystallinity of more than 30% could be produced by high velocity oxygen fuel spraying (HVOF). This is in accordance to prior works where coatings from ceramic materials such as alumina, chromia, titania, or even hydroxyapatite with high degrees of crystallinity and high phase purity could be achieved by HVOF deposition starting from small-sized or nano-agglomerated feedstocks [10][11][12][13] . All studies concluded that dense ceramic coatings can be obtained with sufficient deposition efficiency only if particles are melted sufficiently so that good adhesion between the deposited splats is achieved, while crystallinity in the coating depends mainly on the amount of partially unmelted powder particles.…”
Section: Accepted Articlesupporting
confidence: 90%
“…20 However, attempts to deposit nanofeatured coatings using HVOF have been hampered by the need to obtain sufficient particle soening to successfully form a coating, whilst still retaining the nano-structure within the original powder particles. 21 These attempts were aimed at obtaining coatings with novel tribological properties, rather than superhydrophobicity. In conventional powder feeding, a reduction of the particle size below 5 mm requires specialised powder feeding methods due to the poor owability of such feedstocks, which results from strong agglomeration between particles.…”
Section: Introductionmentioning
confidence: 99%
“…As a down side, the added TiO 2 also decreases hardness and wear resistance of the coating [2]. During the last decade, nanostructured powders have been gaining increasing attention and improved coating properties, e.g., higher toughness, adhesion, and wear resistance, have been reported [4][5][6][7][8]. Typically, Al 2 O 3 and Al 2 O 3 -TiO 2 powders have been manufactured by blending Al 2 O 3 and TiO 2 fused and crushed powders or by cladding Al 2 O 3 particles with TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, the coating properties have been improved by the use of HVOF processes, as well as with the development of nanostructured powders for plasma spraying, i.e., agglomerated and sintered powders from nanosized primary particles. Both, nanostructured coatings and HVOF-sprayed coatings have been reported to possess significantly higher wear resistance compared to conventional plasma-sprayed coatings [4][5][6][7][8]18,19]. However, the performance of nanostructured plasma-sprayed coatings and HVOF-sprayed ceramic coatings has not been truly compared under abrasive, erosive, and cavitation erosion wear.…”
Section: Introductionmentioning
confidence: 99%